PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI ADMINISTRASI DAN RESERVASI ONLINE PADA SLIMMY & BEUATY SPA - Thomas Leman; Rudy Adipranata; Liliana - (Jurnal Infra, 2013)
Slimmy and Beauty Spa is a company which involve and offer a Modern Spa Business. Main target especially woman - middle up class in Surabaya Area. The speciality which differentiate Slimmy & Beauty Spa from other competitor is a "Home Spa" offer. This service give benefit to client which need Therapist visit there place and make them to enjoy this Spa service at their home comfort. Customer only need to make a call and this service could be arranged at their home immediately.The visual website set up was expected to provide all basic information regarding all product offering in their Spa, all Spa services availabe, and also special exclusive package for customers satisfaction. In this curcumstance, so many competitor also offer and provide official website, so this suggestion for on line reservation should be a good and one step ahead of other competition, which offered by writer.Base On quessionaire, almost 90% website result was prepared as per owner need's and special inquiry. This report was accurate and based on actual manual calculation. Additionally, this website design is prepared for friendly user or easy used for administration staff which access it.